A surface deformation method based on stiffness control - Xuzhou QIN; Tieru WU; Yipeng LIU (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
Surface deformation operations commonly require the local details to be preserved as much as possible. In recent years, the As-Rigid-As-Possible(ARAP) shape deformation has gained popularity. Existing ARAP deformation methods define a local cell at each vertex as its 1-ring neighborhoods, and keep the deformation in each local cell as rigid as possible. Since the local cells of adjacent vertices share a single edge, the consistency between adjacent local rigid transformations maintains relative weak. In this paper, we define a new face-based local cell, which expands the overlapping areas between adjacent local cells, thereby enhancing the consistency of adjacent local rigid transformations. Based on this, we further present a stiffness control surface deformation method. The size of the proposed local cell controls global stiffness of the shape. For each local cell, a local stiffness parameter can be specified by the user or can be learned from a set of deforming models automatically to control the local deformation. Through adjusting the size of the local cell and local stiffness parameter, we can generate physically plausible, material-aware deformation results. Based on this local cell, we further propose a shape interpolation method, which has better performance and extrapolation capabilities. Experimental results demonstrate the effectiveness of our method.